A case of brucellosis presenting with acute hepatitis and bicytopenia - Denk, Affan; Ozden, Mehmet (EDIMES Edizioni Medico Scientifiche, 2015)
Although liver involvement is frequently seen in brucellosis, acute hepatitis is a rare clinical entity. In its progress, haematological findings are non-specific and vary in respect to severity. In this paper, we present a case of brucellosis with acute hepatitis and bicytopenia without anaemia. A 19-year-old man presented with a 2-week history of fever, sweating, low back and leg pain, lassitude, loss appetite, nausea and vomiting. He gave a history of raw milk ingestion and animal contact. Physical examination showed signs of icteric skin and sclera, tenderness in the right hypochondriac region and hepatosplenomegaly. On admission to hospital, laboratory tests showed WBC 3500/mm3 (polymorphs 63% and lymphocytes 33%), haemoglobin 13.8 g/dL, platelet 89000/mm3, erythrocyte sedimentation rate 19 mm/h, and C-reactive protein 21.7 mg/ dL (N<0.8 mg/dL). Biochemical tests were as follows: AST 771 U/L, ALT 471 U/L, ALP 355 U/L, GGT 432 U/L, total bilirubin 2.61 mg/dL, direct bilirubin 1.45 mg/dL and albumin 3.7 g/dL. Viral hepatitis markers were found to be negative (HBsAg, anti-HBc total, anti- HBc IgM, anti-HAV IgM, and anti-HCV). Blood culture grew Brucella melitensis. Leukopenia and thrombocytopenia returned to normal levels at the 7th and 14th day of his admission, respectively. Liver function tests improved at the 28th day. Treatment of the brucellosis was performed with antibiotics (tetracycline 500 mg orally four times daily for 6 weeks and streptomycin 1 g IM once daily for 21 days). Finally, a case of brucellosis with acute hepatitis and bicytopenia was treated with a successful outcome. In conclusion, we suggest that due consideration be taken of bicytopenia/pancytopenia and acute hepatitis in brucellosis cases in Turkey, an endemic region. © 2015 EDIMES Edizioni Medico Scientifiche. All rights reserved.
Un caso di brucellosi con presentazione clinica di epatite acuta e pancitopenia
Keywords: Acute hepatitis; Bicytopenia; Brucellosis